Students’ Linguistic Knowledge in Comprehending Defamation Text - Nana Raihana Askurny; Syihabuddin Syihabuddin (Universitas Cokroaminoto Palopo, 2022)
This study is aimed to find out how students’ linguistic knowledge to comprehend defamation text. Defamation is defined as misuse of language to humiliate other person. The researcher took 75 students of sixth semester, of English Education study program, of Unversitas Raja Ali Haji, Tanjungpinag, as the research participant. This research employed qualitative design with aaplying calculation to assert the result. The data was collected by a set of questions which consists of 13 multiple choice questions. The validiy test had been conducted before the data gathering. The linguistic knowledge in this study were limited with semantic and pragmatic. The result shows that semantic and pragmatic knowledge of the students were not adequate, which means that, the students need to develop their knowledge of linguistic by improving their text comprehension.